Application of K-Means Algorithm in Grouping Households Accessing the Internet by Province - Syahara, Zahra; Saifullah; Jalaluddin (Yayasan Kita Menulis, 2021)
The study aims to group households that access the Internet according to the province. As for the data source in this study was made from BPS (the statistical center body) and the data used in the study was in 2017 to 2019 isolated from 34 provinces in Indonesia. The method of artificially synthesizing the research is using a k-means algorithm. According to the data, groups of households that access the Internet according to the provinces are grouped into 2 clusters of high clusters (c1) and low cluster (c2). It is hoped that this study will provide more attention to the government for the provinces that have low Internet access, It could also lead to programs that would seek to improve people's access to the Internet via e-government, telencenter, smart villages, or smart city, and indonesian-to pursue their relationship with more advanced Internet countries such as Europe and America